2010
DOI: 10.1007/s12245-010-0162-3
|View full text |Cite
|
Sign up to set email alerts
|

Is it safe to use propofol in the emergency department? A randomized controlled trial to compare propofol and midazolam

Abstract: BackgroundThis study examined the safety and effectiveness of the procedural sedation analgesia (PSA) technique carried out in the emergency department (ED) of a university hospital over a period of 1 year. The research was done to compare the effectiveness and efficacy of moderate sedation of fentanyl combined with either midazolam or propofol for any brief, intense procedure in the ED setting.AimsThe objectives were to observe the occurrence of adverse events in subjects undergoing PSA for intense and painfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…No correlation was observed between the type of drug (midazolam, propofol, and their combinations) and the presence of complication in the present study, which was consistent with other similar studies. [9,[16][17][18][19] According to the present study and other previous studies, the sedation level determined the risk of complication in PSA rather than the type or dose of the drug. It can be concluded that effective PSA monitoring reduces the risk of complications irrespective of the drug dose.…”
Section: Discussionsupporting
confidence: 62%
“…No correlation was observed between the type of drug (midazolam, propofol, and their combinations) and the presence of complication in the present study, which was consistent with other similar studies. [9,[16][17][18][19] According to the present study and other previous studies, the sedation level determined the risk of complication in PSA rather than the type or dose of the drug. It can be concluded that effective PSA monitoring reduces the risk of complications irrespective of the drug dose.…”
Section: Discussionsupporting
confidence: 62%
“…Age could not be stratified because the subjects recruited were adults in the study of Rahman and Hashim [34], while age and psychological maturity can affect emergence agitation in the study of Picard and his colleagues [3]. Minor complications were recorded in children under 16 years, all patients with intellectual disability in the study of Ransford and his colleagues [21].…”
Section: Discussionmentioning
confidence: 99%
“…Among randomized studies,[11121314151617181920212223242526] the outcomes investigated are heterogeneous. Furthermore, the doses and also the professional leading the anesthesia were different in many cases, which could have influenced their results [Table 2].…”
Section: Propofol For Direct Current Cardioversionmentioning
confidence: 99%
“…[15161718] When compared with midazolam, one study showed that the decrease in systolic blood pressure was more pronounced with propofol,[19] while others did not report difference. [10131420] It must be highlighted that even in studies that presented statistically significant reduction in blood pressures, no relevant clinical effect was found. In addition, elderly patients with structural heart diseases showed to be more prone to hypotension, especially when fentanyl was administrated along with propofol.…”
Section: Propofol For Direct Current Cardioversionmentioning
confidence: 99%